دور التسويق الإلكتروني في تحسين الأنشطة التسويقية للمصارف الإسلامية دراسة إحصائية باستخدام نمذجة المعادلات الهيكلية (SEM-PLS): The role of electronic marketing in improving the marketing activities of Islamic banks -A Statistical study using structural equation modeling (SEM-PLS)- - لعبيدي سامي (Journal of North African Economies, 2025)
This study aimed to determine the role of e-marketing in improving the marketing activities of Islamic banks, and based on previous studies, a conceptual model was developed and clarified that integrates the dimensions of e-marketing represented in (e-marketing resources, e-marketing strategies) and how it affects marketing activities, whether before or after the provision of Islamic banking services. To achieve the objectives of the study, the study model was tested in the field on Al-Salam and Al-Baraka Banks in Algeria, where the questionnaire was relied upon as a tool for collecting data from a sample of 150 administrative employees from the banks under study, and the data was processed using structural equations modeling according to the partial least squares method (SEM-PLS). The study concluded that there is a positive impact of adopting electronic marketing on improving the marketing activities of Islamic banks.